Arsenic detection in water: YPO4:Eu3+ nanoparticles - Ghosh, Debasish; Luwang, Meitram Niraj (Journal of Solid State Chemistry, 2015)
This work reports on the novel technique of detection of arsenic in aqueous solution utilising the luminescence properties of lanthanide doped nanomaterials. Eu3+ (5%) doped YPO(4)nanorodswere utilised for the said experiment. Co-precipitation method was used for the synthesis of the materials and characterised them with different instrumental techniques like X-ray diffraction (XRD), Infra-red (IR), UV-absorption, scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS) and photoluminescence studies. This nanoparticle can adsorb both arsenic and arsenious acids. We studied the effect of arsenic adsorption on the luminescence behaviour of the nanoparticles. Arsenic acid enhanced the luminescence intensity whereas arsenious acid quenched the luminescence. This luminescence enhancement or quenching is related with arsenic concentration. This relation of luminescence property with concentration of arsenic can be used to detect arsenic in industrial waste. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Arsenic detection; Luminescence; Nanomaterials